Determination of the transcriptomic effects and compensatory role ofF INHA C-15T promoter mutation in mycobacterium tuberculosis. - Mwendwa, Leah Kalekye (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.